An Application of Two Binary Choice Models as Credit Scoring Tools for Philippine LGU-Borrowers - Pasimio, Winona S. (Philippine Management Review, 2016)
This paper presents the empirical results of applying two binary choice models as credit scoring tools for evaluating the creditworthiness of local government units (LGUs) in the Philippines.  Credit scoring is a quick and economical way of evaluating risk especially when there is a large number of potential borrowers.  The study’s findings suggest that good LGU payors exhibit quite distinct financial characteristics from poor LGU payors.  Both models reveal that the percentage rate of change of total revenue is the single most important factor associated with credit-servicing performance.  The findings indicate that quantitative credit scoring models can be employed to assess the creditworthiness of Philippine LGUs.